Reliability Modeling and Verification of Locking Mechanisms Based on Failure Mechanisms - Ping Qian; Tianying Tu; Wenhua Chen; Fan Yang; Chi Chen; Yucheng Zhu (Actuators)
The locking mechanism is crucial for the reliable connection and disconnection of electrical connectors. Aiming at the lack of theoretical support for the reliability evaluation in long-term storage, a comprehensive multi-theory modeling method is proposed to solve unlocking failure and related performance-evaluation problems. An analysis reveals that metal-crystal dislocation glide, causing pull-rod deformation and spring stress relaxation, is the main cause of unlocking failure. Based on Hertz’s contact theory, a locking-state mechanical model is established. Integrating the crystal dislocation-slip theory, an accelerated degradation trajectory model considering design parameters is developed to characterize the friction between the pull rod and steel ball and the spring’s elastic-force degradation. Finally, the model is verified using the unlocking-force accelerated test data. It offers a theoretical basis for the reliability evaluation and design of locking mechanisms in long-term storage environments.